Inhibition of thioredoxin reductase 1 by caveolin 1 promotes stress-induced premature senescence - Volonte, Daniela (Nature Publishing Group, 2009)
Thioredoxin reductase 1 (TrxR1) is an important antioxidant enzyme that controls cellular redox homeostasis. By using a proteomic-based approach, here we identify TrxR1 as a caveolar membrane-resident protein. We show that caveolin 1, the structural protein component of caveolae, is a TrxR1-binding protein by demonstrating that the scaffolding domain of caveolin 1 (amino acids 82–101) binds directly to the caveolin-binding motif (CBM) of TrxR1 (amino acids 454–463). We also show that overexpression of caveolin 1 inhibits TrxR activity, whereas a lack of caveolin 1 activates TrxR, both in vitro and in vivo. Expression of a peptide corresponding to the caveolin 1 scaffolding domain is sufficient to inhibit TrxR activity. A TrxR1 mutant lacking the CBM, which fails to localize to caveolae and bind to caveolin 1, is constitutively active and inhibits oxidative-stress-mediated activation of the p53/p21(Waf1/Cip1) pathway and induction of premature senescence. Finally, we show that caveolin 1 expression inhibits TrxR1-mediated cell transformation. Thus, caveolin 1 links free radicals to activation of the p53/p21(Waf1/Cip1) pathway and induction of cellular senescence by acting as an endogenous inhibitor of TrxR1.